Faktor-Faktor yang Berhubungan dengan Kepemimpinan Kepala Ruangan Dalam Pengelolaan Krisis Covid-19 Di Rumah Sakit Kota Padang Tahun 2022 - Rani Permata Sari; Yulastri Arif; Lina Febrianti (Universitas Batanghari Jambi, 2022)
The occurrence of a crisis situation caused by COVID-19 forces the head of the room to adjust its leadership to the conditions of the preparation, implementation, and evaluation during the COVID-19 crisis situation so that it can run the survival of an inpatient room. This study aims to determine the